2023
DOI: 10.1101/2023.05.12.540367
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Highly pathogenic avian influenza causes mass mortality in Sandwich tern (Thalasseus sandvicensis) breeding colonies across northwestern Europe

Ulrich Knief,
Thomas Bregnballe,
Ibrahim Alfarwi
et al.

Abstract: In 2022, highly pathogenic avian influenza (HPAI) A(H5N1) virus clade 2.3.4.4b became enzootic and caused mass mortality in Sandwich terns and other seabird species across northwestern Europe. We present data on characteristics of the spread of the virus between breeding colonies and the number of dead adult Sandwich terns recorded at breeding sites throughout northwestern Europe. Within two months after the first mortalities were reported, in total 20,531 adult Sandwich terns were found dead, which is >17%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The latter have been hit severely by HPAIV H5, culminating even in mass mortalities (Anne Pohlmann et al, 2023). Removal of possibly HPAIV-infected carcasses by human activities has been shown to have positive effects on such colonies (Knief et al, 2023). Yet, this kind of carcass removal can never be as efficacious (and timely) as the scanning activities of birds of prey.…”
Section: Discussionmentioning
confidence: 99%
“…The latter have been hit severely by HPAIV H5, culminating even in mass mortalities (Anne Pohlmann et al, 2023). Removal of possibly HPAIV-infected carcasses by human activities has been shown to have positive effects on such colonies (Knief et al, 2023). Yet, this kind of carcass removal can never be as efficacious (and timely) as the scanning activities of birds of prey.…”
Section: Discussionmentioning
confidence: 99%
“…The relative low number of fulmars collected in year 2022 is mainly a consequence of the major outbreak of highly pathogenic avian influenza (HPAI) in seabirds. Considerable mortality was observed among great skuas (Stercorarius skua), Sandwich terns (Thalasseus sandvicensis) and northern gannets (Morus bassanus) in the UK (Camphuysen et al 2022;Lane et al 2023;Knief et al 2023).…”
Section: Modelling Trendsmentioning
confidence: 99%
“…During the 2022 breeding season, > 20,000 Sandwich Terns ( Thalasseus sandvicensis ) were found dead across Europe, comprising > 17% of the total northwestern European breeding population. In addition to the adult birds, within colonies, almost all chicks died (Knief et al 2023). Northern Gannets ( Morus bassanus ) were similarly heavily affected in the Atlantic, with unusually high mortality at colonies, including at Bass Rock in Scotland where the number of occupied nests decreased by 71% (Lane et al 2023).…”
Section: Waterbird Populations Are Negatively Impacted By the Current...mentioning
confidence: 99%
“…A key feature of all HPAI outbreaks to date is the prioritization of response towards poultry, such that there is almost no, or limited information pertaining to waterbird outbreaks. For example, of the ∼20,000 Sandwich Terns reported in (Knief , et al 2023), only 68 were reported to the World Organisation for Animal Health (Klaassen and Wille 2023). Mortality data from wild bird outbreaks are critical for population assessments, conservation plans, International Union for Conservation of Nature (IUCN) status etc, so this mismatch between reports from the ground and notifications to the most comprehensive database is highly concerning.…”
Section: How To Weather the Storm?mentioning
confidence: 99%